Genome-wide Core Proteome Analysis of Brucella melitensis Strains for Potential Drug Target Prediction - Rahman, Noor; Shah, Mohibullah; Muhammad, Ijaz; Khan, Haroon; Imran, Muhammad (Mini Reviews in Medicinal Chemistry, 2021)
Introduction: Brucella melitensis is a facultative intracellular bacterial pathogen that causes abortion in goats and sheep and Malta fever in humans. In humans, chronic infection occurs through contact with infected animals or their waste products. Methods: The subtractive genomic approach is considered as a powerful and useful method for the identification of potential drug and vaccine targets. In this study, an attempt has been made through a subtractive proteomic strategy to identify novel drug targets in Brucella melitensis strains. Total 2604 core proteins of 56 strains of B. melitensis were taken, of which 545 non-human homologs were found to be essential for pathogen growth. Metabolic pathway analysis of these essential proteins revealed that 129 proteins are exclusively involved in 21 unique metabolic pathways in B. melitensis reference strain. Results: Of these, 31 proteins were found to be involved in 10 metabolic pathways that are unique to the pathogen. We selected Nitrate reductase subunit-β, Urease subunit α-2, Pantoate-β-alanine ligase, Isochorismatase, 2-dehydro-3-deoxyphosphooctonate aldolase and Serine O-acetyltransferase as drug targets in Brucella melitensis strains. Among these druggable targets, we selected only Pantoate-β- alanine ligase as high confidence target based on intensive literature curation, which is nonhomologous to the human gut metagenome involved in biosynthesis of secondary metabolites pathway. Pantothenate synthetase is the best chemotherapeutic target to combat Brucellulosis. Conclusion: Furthermore, in vitro and in vivo validation is needed for the evaluation of lead compounds against Brucella melitensis strains.
Keywords: chemotherapeutic